Exploring Muslim consumers' confidence and awareness towards halal labeled manufactured food products in Sabah - Md Sawari, Siti Salwa; Sahar, Rafidah; Omar, Intan Marfarrina (2018)
This paper focuses on the Muslim consumers’ confidence and awareness towards halal labelled manufactured food products. A qualitative study was chosen as a research design to gather information about the Muslim consumers’ attitude on halal labels for manufactured food products in Sabah. Structured interviews were conducted with seven Muslim consumers. The interviews were then content analysed, and an inventory was formed. Findings of the study indicate that the Muslim consumers were confident with the halal labelled manufactured food products. The findings also show that the Muslim consumers were less aware of the authorities responsible for the certification of halal labels in Sabah. This paper contributes to a better understanding of the Muslim consumer attitude relating to the labels of halal food products. Moreover, this paper helps to emphasise some of the main issues that frame the current state of halal labelled manufactured food products in Sabah.